1998
DOI: 10.3109/00207459808986411
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of a body image disorder (Macrosomatognosia) in parkinson's disease by treatment with ac pulsed electromagnetic fields

Abstract: Macrosomatognosia refers to a disorder of the body image in which the patient perceives a part or parts of his body as disproportionately large. Macrosomatognosia has been associated with lesions in the parietal lobe, particularly the right parietal lobe, which integrates perceptual-sensorimotor functions concerned with the body image. It has been observed most commonly in patients with paroxysmal cerebral disorders such as epilepsy and migraine. The Draw-a-Person-Test has been employed in neuropsychological t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…In a study that evaluated hemiplegic individuals through "The My Body Image Test", these individuals presented impairment in body image perception 21 . The impairment in the body perception and body consciousness observed in these subjects could be due to somatosensoral and motor-perception problems that are relatively common in cerebral injuries due to what is call "perceptual confusion", a disorder in the body image due to the difficulty in perceiving or interpreting sensory input 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study that evaluated hemiplegic individuals through "The My Body Image Test", these individuals presented impairment in body image perception 21 . The impairment in the body perception and body consciousness observed in these subjects could be due to somatosensoral and motor-perception problems that are relatively common in cerebral injuries due to what is call "perceptual confusion", a disorder in the body image due to the difficulty in perceiving or interpreting sensory input 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Put in all the numbers and set the time to 10 after 11.” Draw Your Pelvis test (Abraham et al, unpublished data; Abraham et al, )—a drawing test designed for quantitatively assessing pelvic schema in people with PD. The test is based on the Human Figure Drawing test (Riklan, Zahn, & Diller, ; Sandyk, ) and other drawing assessment methods for conditions associated with specific body parts (Moseley, ). The participant sat on a chair in front of a desk and was asked to draw a freehand rear view of his/her own pelvis (Figure ) using a black ink pen on a half blank A4 page with no frame.…”
Section: Methodsmentioning
confidence: 99%
“…As cognitive impairments are among the common characteristics of PD (De Pandis et al, ; Levin et al, ), this test is suitable for people with PD and is commonly used for PD screening (De Pandis et al, ; Pinto & Peters, ). As people with PD may also exhibit with a distorted body schema (Gamarra et al, ; Sandyk, ), and given that drawing tests can not only reflect cognitive and motor status but also how the stereotypical image of a drawn object is represented in the mind (Anderson, ; Zoltan, Siev, & Freishtat, ); the drawing of a body or its parts may be helpful in evaluating a specific aspect of cognitive status–body schema (Freund, Gravenstein, Ferris, Burke, & Shaheen, ; Moseley, ) in people with PD (Sandyk, ). Although not thoroughly investigated to date, it has been suggested that PD characteristics play a role in body schema misperceptions, and thus potentially exhibited in drawings (Bissolotti et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported PEMF therapy improved cognitive functions and motor symptoms. For example, an investigation involving three elderly PD patients with cognitive impairment assessed the effect of PEMF therapy on macrosomatognosia, a disorder of the body image in which the patient perceives a part or parts of his body as disproportionately large [ 135 ]. After receiving PEMF therapy, PD patients’ drawings showed reversal of macrosomatognosia (assessed by Draw-a-Person test) with reduction of the right parietal lobe dysfunction.…”
Section: Pulsed Electromagnetic Field Therapymentioning
confidence: 99%